Pm-EEMRP: Postural Movement Based Energy Efficient Multi-hop Routing Protocol for Intra Wireless Body Sensor Network (Intra-WBSN) - Tarique Rashid; Sunil Kumar; Akshay Verma; Prateek Raj Gautam; Arvind Kumar (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Intra-WBSN plays an important role in health monitoring, military and consumer electronics. It iscomposed of wireless bio-sensor nodes which are strategically placed on the body. Due to body posture movement, network topology of Intra-WBSN changes continuously. It plays a significant role in Intra-WBSN. In proposed Pm-EEMRP, network stability, energy efficiency and high throughput are the prime parametersfor body posture movement in which sensing informations from bio-sensor nodes are forwarded to relay nodes. Relay nodesare deployed in cloths, which aggregate these data and forward it to body network controller (BNC). It provides reliable and comfortable health monitoring. Through simulation, the proposed routing protocol provides better network stability, improved energy efficiency and high throughput in comparison to conventional routing schemes.